Pengaruh Aroma Terapi Jahe Terhadap Mual Muntah Pada Ibu Hamil Trimester I: Pengaruh Aroma Terapi Jahe Terhadap Mual Muntah Pada Ibu Hamil Trimester I - Sellia Juwita; Nova Yulita; Jumiati Jumiati (LPPM Universitas Abdurrab, 2023)
ABSTRACT Nausea and vomiting occur in 60-80% of primigravida and 40-60% of multigravidarum. In one hundred out of a thousand pregnancies these symptoms become more severe. The incidence of emesis gravidarum in Indonesia is 50-90% in pregnancy. However, in cases like this it does not cause death in pregnant women because it only lacks nutrition and fluids. If hyperemesis gravidarum occurs, a pregnant woman will find it difficult to consume food and this will result in malnutrition and can disrupt fetal growth. The aim of this study was to determine the effect of ginger aromatherapy on nausea and vomiting in pregnant women. The research design used in this research is quantitative research using an experimental research design. The population in this study was TM 1 pregnant women using a total sampling technique with a total sample of 24 respondents. Data analysis used univariate analysis and bivariate analysis using the paired sample T-Test. The results of the univariate analysis showed that after receiving ginger aromatherapy intervention, the majority of pregnant women did not experience nausea and vomiting, 70.8%, and the bivariate analysis results showed a p-value of 0.000 < Î±= 0.05, which means that there was an effect of ginger aromatherapy on nausea and vomiting in pregnant women in the Rumbai health center working area.